(untitled) (Mustansiria Dental Journal, 2018)
Saliva is an easily collected fluid that contains locally and systemically derived markers of periodontal disease. The purpose of this study was to compare the level of salivary alkaline phosphatase activity in healthy subjects and patients with periodontal disease (gingivitis and periodontitis), and to evaluate the relationship of this enzyme with different clinical parameters in all patients included in the study. The study included 65 patients referred to Department of Oral Diagnosis, College of Dentistry, University of Baghdad, they were divided into three groups, 20 healthy subjects, 20 subjects with gingivitis and 25 one with periodontitis. The clinical parameters including plaque index (PI), gingival index (GI), probing pocket depth (PPD) and clinical attachment loss (CAL) were recorded and salivary samples collected for analysis of alkaline phosphatase (ALP) levels. A highly significant increase in mean values of clinical parameters was found in patients with periodontal disease (gingivitis and periodontitis) compared to healthy subjects, also a highly significant increase in the mean values of alkaline phosphatase activity was illustrated as the severity of periodontal disease increased. ALP level was closely related to the gingival index, probing depth and attachment loss in patients with periodontal disease, while no relation was shown to plaque index. Salivary alkaline phosphatase could be used as a useful marker for monitoring periodontal disease.